Analisis Perbedaan Penggunaan Transaksi Tunai Dan Non Tunai (E-Money) Pada Mahasiswa UPN “Veteran” Jawa Timur - Diva Shafitri; M Taufiq (CV. Ulil Albab Corp, 2022)
Money is something important in a country. Due to the rapid development of money in Indonesia, the payment system is also growing into two parts, cash and non-cash payments. Students also use it. However, differences in gender, UKT group, and area of ​​residence can affect the differences in transactions between each other. Therefore, this study discusses the differences in the frequency of transactions and the nominal value of transactions at UPN